HUBUNGAN RELIGIUSITAS DAN LABELISASI HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK NON MAKANAN DAN MINUMAN - Nugroho, Wahyu Adi; Anwar, Moch Khoirul (Universitas Negeri Surabaya, 2020)
The need for halal status and product safety has led to the emergence of the Halal Product Guarantee Act (JPH Law). With the JPH Law, not only food and beverages must be halal certified, but also non-food and beverage products, including cosmetic products and used goods. The purpose of this study is to find out how the relationship between religiosity and halal labeling on purchasing decisions for non-food and beverage products, specifically cosmetic products and used goods. This research is a quantitative study with a total sample of 140 people with data collection using a questionnaire. Data analysis used multiple correlation analysis test, partial test (t test), simultaneous test (f test), and coefficient of determination test (R2 test). The results showed that the religiosity variable had a positive and significant relation on purchasing decisions and the halal labeling variable also had a positive and significant relation. While the test results of the coefficient of determination (R2) are at a value of 55.7% meaning that the variable religiosity and halal labeling contribute to 55.7% of the decision to purchase non-food and beverage products.